PENGARUH KECERDASAN INTELEKTUAL, EMOSIONAL DAN SPRITUAL TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI DALAM PRAKTIK PELAPORAN KEUANGAN - -, Arisman; -, Darmuji (InFestasi, 2019)
This aims of this sudy was to obtain empirical evidence about the influence of intel-lectual intelligence, emotional intelligence and spiritual intelligence to ethical behavior accounting students in financial reporting practices. The population of this research was 37 accounting students at the Jambi Polytechnic. The data analysis technique used is simple linear regression analysis and multiple linear regression analysis. The results of this study indicate that intellectual intelligence, emotional intelligence and spiritual intelligence positively influence the ethical behavior of accounting students in financial reporting practices.